Pengaruh Curent Ratio, Debt to Equity Ratio, Total Asset Turnover Terhadap Perubahan Laba - Yudhi Priyono; Hadi Samanto; Sumadi Sumadi (Jurnal Akuntansi dan Pajak, 2022)
This study aims to influence the current ratio (CR), debt to equity ratio (DER), and total asset turnover (TATO) on changes in profits at manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This type of research is quantitative research, with secondary data sources taken from www.idx.co.idin 2017 to 2019. Sampling techniques using purposive sampling so that 28 companies obtained with 84 observations of financial statements manufatur company. Data techniques use multiple linear regression analysis. The results showed that each variable current ratio, debt to equity, total asset turn over affects the change in profit. Current ratio, debt to equity, total asset turn over jointly affects the change in profit